2017
DOI: 10.1097/mat.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

Infection, Oxidative Stress, and Changes in Circulating Regulatory T Cells of Heart Failure Patients Supported by Continuous-Flow Ventricular Assist Devices

Abstract: The objective of this study was to investigate the changes in oxidative stress (OS) and circulating regulatory T cells (Tregs) of the immune system in CF-VAD patients with or without infection. We recruited 16 CF-VAD patients (5 with infection and 11 without infection) and 7 healthy volunteers. Generation of reactive oxygen species (ROS) from lymphocytes, superoxide dismutase (SOD) in erythrocyte, total antioxidant capacity (TAC) and oxidized low density lipoprotein (oxLDL) in plasma were measured. Circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The one available study showed increased apoptotic activity in CD4 + T cells up to 4 weeks post-operatively which normalised to baseline after 7 weeks (45) rather than sustained excessive CD4+ T cell apoptosis linked to a drastic reduction in circulating CD4+ T cells in pulsatile devices (20). More recently, a study of infection rates in continuous flow VAD (CF-VAD) patients found that patients with infection had much higher numbers of circulating regulatory T (Treg) cells than those without infection (46). Oxidative stress was also prominent in CF-VAD patients and combined with increased Treg cells could lead to immunosuppression and pathogen persistence (46).…”
Section: Vad Use Can Lead To Immunosuppressionmentioning
confidence: 99%
“…The one available study showed increased apoptotic activity in CD4 + T cells up to 4 weeks post-operatively which normalised to baseline after 7 weeks (45) rather than sustained excessive CD4+ T cell apoptosis linked to a drastic reduction in circulating CD4+ T cells in pulsatile devices (20). More recently, a study of infection rates in continuous flow VAD (CF-VAD) patients found that patients with infection had much higher numbers of circulating regulatory T (Treg) cells than those without infection (46). Oxidative stress was also prominent in CF-VAD patients and combined with increased Treg cells could lead to immunosuppression and pathogen persistence (46).…”
Section: Vad Use Can Lead To Immunosuppressionmentioning
confidence: 99%
“…Lymphocytes are affected by both pulsatile and CF-VADs [13][14][15]. A general lymphopenia occurred in patients, implanted with the early pulsatile HeartMate XVE [14].…”
Section: Leukocytesmentioning
confidence: 99%
“…Patients with CF-VADs also have changes in their T cell levels. However, contrary to pulsatile LVAD-patients, those implanted with CF-VADs (specific device not published) and who suffered from infection had significantly higher levels of CD4+/CD25+ Tregs and increased lymphocyte reactive oxygen species (ROS) compared to VAD-patients without infection [13]. Whether these differences between pulsatile and CF VADs relates to pulsatility would be an interesting topic for further studies.…”
Section: Leukocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-physiological high shear stress has been suggested to contribute to the shedding of key platelet receptors [1719]. Studies also reported that oxidative stress may also influence the alteration of platelet and leukocyte functionality in CF-LAVD patients with systemic inflammation, infection and sepsis [20,21]. Oxidative stress and peroxide synthesized in the platelet lipoxygenase pathway activates tumor necrosis factor-alpha-converting enzyme and induce shedding of key platelet receptors in murine and human model [22].…”
Section: Introductionmentioning
confidence: 99%